Multimedia group communication : - Rebeiro-Hargrave, Andrew (John Wiley & Son, 2008)
This book provides an in-depth overview of Multimedia Group Communications in the mobile domain. It specifies multimedia group communication concepts, introduces a range of applications, and proposes an evolution path. The concepts cover the "walkie-talkie" voice over IP service, XML list management, and Presence awareness technologies. The applications section embraces session control for closed professional groups and for open consumer groups. The evolution path includes exciting developments such as ‘infotainment’ and communication with non-human group members